Integrated Cash Waqf-Linked Sukuk (CWLS) Models: Islamic Blended Finance Framework for Waste-to- Alternative Energy Projects in Indonesia - Rindawati Maulina; Imam Nur Azis; Jaharuddin Jaharuddin (Badan Wakaf Indonesia, 2026)
Environmental issues, especially in waste management, remain largely unresolved in many countries, including Indonesia, often due to financing constraints. However, Indonesia possesses a cash waqf-based Islamic financial instrument that could serve as a capital source for sustainable waste management projects. In this country, the integration of cash waqf with Islamic financial instruments and commercial institutions has already been developed in the form of cash waqf-linked sukuk (CWLS), although its primary objective is currently still focused on social needs. To address this research gap, this study aims to develop an integrated financing model that combines CWLS with other Islamic finance instruments. The goal is to fund waste management projects through an Islamic blended finance framework, with a specific emphasis on sustainable and alternative energy source. This study takes a qualitative approach using a document review method to serve as a preliminary step. This initial analysis guides the creation of a policy blueprint for relevant stakeholders. For future research, in-depth interviews and Focus Group Discussions (FGDs) could be used to further explore and understand the proposed model's feasibility and the readiness of all involved actors.